2021
DOI: 10.1155/2021/9933236
|View full text |Cite
|
Sign up to set email alerts
|

A Network Pharmacology Approach to Investigate the Mechanism of Erjing Prescription in Type 2 Diabetes

Abstract: Erjing prescription (EJP) was an ancient formula that was recorded in the General Medical Collection of Royal Benevolence of the Song Dynasty. It has been frequently used to treat type 2 diabetes mellitus (T2DM) in the long history of China. The formula consists of Lycium barbarum L. and Polygonatum sibiricum F. Delaroche with a ratio of 1 : 1. This study aimed to identify the potential effects and mechanisms of EJP treatment T2DM. The target proteins and possible pathways of EJP in T2DM treatment were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Based on a computer prediction method to calculate the identified compounds of apple pollen, this study obtained absorption parameters that could determine whether the chemical compositions could be absorbed. Table 3 showed the specific absorption parameters of all of the components [ 26 ]. The data indicated that there were a total of 18 chemical compositions (Figures 3 and 4 ) that satisfied the principles of drug absorption (GI absorption is high and at least two of the five Druglikeness were yes).…”
Section: Resultsmentioning
confidence: 99%
“…Based on a computer prediction method to calculate the identified compounds of apple pollen, this study obtained absorption parameters that could determine whether the chemical compositions could be absorbed. Table 3 showed the specific absorption parameters of all of the components [ 26 ]. The data indicated that there were a total of 18 chemical compositions (Figures 3 and 4 ) that satisfied the principles of drug absorption (GI absorption is high and at least two of the five Druglikeness were yes).…”
Section: Resultsmentioning
confidence: 99%
“…55 The AKT protein is a core downstream factor of insulin/PI3K/AKT signalling, 56,57 is widely expressed in insulin-sensitive tissues, and can regulate glucose metabolism by inducing downstream molecules such as Glut to enhance glucose uptake. 58,59 Cell apoptosis is also an important factor in the development of diabetes, and CASP3, currently the most important executioner protein of the caspase cascade signal pathway, is widely used as a biomarker for apoptosis. 60,61 Drosophila melanogaster is an invaluable model organism, offering insights into glucose and lipid metabolism disorders stemming from IR and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Polygonatum sibiricum is a traditional medicinal herb and a functional food in China [ 6 ]. Increasing evidence indicates that P. sibiricum or Chinese medicine compounds containing P. sibiricum can regulate blood sugar levels in animal models [ 7 , 8 ]. P. sibiricum polysaccharides (PSP), important active compounds in PS, are responsible for a broad spectrum of functions, including improved immunity and anti-fatigue, anti-oxidant, anti-aging, and anti-inflammatory effects [ 9 ].…”
Section: Introductionmentioning
confidence: 99%